Ukuran Perusahaan Memoderasi Pengaruh DAR, TATO, CR Terhadap Pertumbuhan Laba Perusahaan Sektor Aneka Industri - Hafiana Anggraini Lubis (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2025)
This research aims to determine the effect of Debt to Asset Ratio, Total Asset Turnover, and Current Ratio on Profit Growth with Firm Size as a moderating variable in various industrial sub-sector manufacturing companies listed on the Indonesia Stock Exchange in 2018 - 2022. The sample selection method used is purposive sampling. The total observations in this study were 51 companies consisting of 20 companies. The data analysis technique used in this research is Moderated Regression Analysis with a residual test approach with the SPSS version 26 analysis toolThe test results of this research indicate that simultaneously Debt to Asset Ratio, Current Ratio, Return On Asset, and Firm Size affect Profit Growth. Partial test results show that Debt to Asset Ratio and Current Ratio have a positive and significant effect on Profit Growth, while Total Asset Turnover has no effect on Profit Growth. The results of the Moderated Regression Analysis test show that Firm Size is able to moderate the effect of Debt to Asset Ratio on Profit Growth, while Firm Size is unable to moderate Current Ratio and Total Asset Turnover on Profit Growth.